Expression and function of human macrophage heparan sulfate proteoglycans - Collins, LE (2021)
Among the hundreds of ligands for heparan sulfate (HS) are chemokines, cytokines, and growth factors, giving this proteoglycan a potentially central role in the regulation of immune responses. The biosynthesis of HS is regulated during inflammation with consequent changes to ligand binding and activity in multiple cell types including myeloid cells. In this thesis, I aimed to comprehensively describe the changes in expression of HS core proteins and biosynthetic enzymes in human primary monocytes and polarised monocyte-derived macrophages, and to investigate the contribution of HS proteoglycans to macrophage functions. Using a custom-designed microfluidic array card, I performed transcriptome analysis of HS-associated gene expression and discovered significant changes at all stages of macrophage maturation and polarisation, revealing that maturation is associated with increased capacity for HS biosynthesis and that pro- and anti-inflammatory macrophages have substantially different HS composition. Of particular interest was the reciprocal regulation observed between the 6-O-sulfotransferase (HS6ST1) and its functional partner the sulfatase (SULF2), which add and remove the 6-O-sulfate group to HS chains, respectively. Using siRNA knockdown of HS6ST1 in monocyte-derived macrophages to ablate 6-O-sulfation of HS, I determined that this modification does not contribute to phagocytosis or migration. Moreover, its absence did not affect macrophage polarisation, whereas total sulfate ablation using sodium chlorate did, suggesting that sulfate modifications at other positions are more important. HS6ST1 knockdown altered post-translational regulation of monocyte chemoattractant protein 1 (MCP-1), indicating the 6-O-sulfate group of HS modulates retention of this and potentially other mediators on the cell surface.